2019
DOI: 10.1115/1.4042652
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of the Impact of Mixed Flow Turbine Inlet Cone Angle and Inlet Blade Angle

Abstract: Mixed flow turbines (MFTs) offer potential benefits for turbocharged engines when considering off-design performance and engine transient behavior. Although the performance and use of MFTs are described in the literature, little is published on the combined impact of the cone angle and the inlet blade angle, which are the defining features of such turbines. Numerical simulations were completed using a computational fluid dynamics (CFD) model that was validated against experimental measurements for a baseline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The maximum mesh y+ value achieved was below 11, and for the majority of the surfaces the y+ value was resolved to below 3. To maintain continuity with existing hardware on the QUB cold flow test rig, the geometry and meshes for the pre-swirl vanes and exhaust diffuser were carried over from a previous study at QUB which had already conducted a grid independence study and validation with experimental results [15]. The numerical model used in this study also closely matched that used by Leonard et al [15] as this modelling approach demonstrated good agreement with experimental results.…”
Section: Numerical Modelmentioning
confidence: 84%
See 2 more Smart Citations
“…The maximum mesh y+ value achieved was below 11, and for the majority of the surfaces the y+ value was resolved to below 3. To maintain continuity with existing hardware on the QUB cold flow test rig, the geometry and meshes for the pre-swirl vanes and exhaust diffuser were carried over from a previous study at QUB which had already conducted a grid independence study and validation with experimental results [15]. The numerical model used in this study also closely matched that used by Leonard et al [15] as this modelling approach demonstrated good agreement with experimental results.…”
Section: Numerical Modelmentioning
confidence: 84%
“…The numerical analysis employed the shear stress transport (SST) turbulence model, as it has provided good agreement with experimental test results in previous studies at QUB [15,16]. The meshes used in the numerical analysis consisted only of structured hexahedral elements.…”
Section: Numerical Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…CFX ® 16.0 was applied to solve Reynolds-averaged Navier–Stokes equations and shear-stress transport (SST) two-equation turbulence model which has been extensively used in the studies of turbomachinery. 15,19,20 The computational model of the turbine included turbine housing, the full 360° channel of the rotor, and the backdisc cavity and solid regions of the turbine. Frozen-rotor method was employed at the rotor–stator (housing) interface.…”
Section: Numerical Model and Verificationmentioning
confidence: 99%
“…ANSYS-CFX 16.0 was used to solve the full three-dimensional N-S equations. An SST-kω two-equation turbulence model, which has been widely tested and verified for use with turbines, was selected for the turbulence model [10,16,17]. A frozen-rotor method was used to process the data transfer between the turbine channel domain and the turbo wheel channel domain.…”
Section: Numerical Modelmentioning
confidence: 99%